2022
DOI: 10.1155/2022/2316666
|View full text |Cite
|
Sign up to set email alerts
|

Concentrated Growth Factors Combined with Lipopolysaccharide Stimulate the In Vitro Regenerative and Osteogenic Activities of Human Dental Pulp Stem Cells by Balancing Inflammation

Abstract: Aim. We investigated the long-term effects of exposure to concentrated growth factors (CGFs) on the regenerative properties of dental pulp stem cells (DPSCs) in the presence and absence of lipopolysaccharide (LPS) as a proinflammatory agent. Methods. DPSCs were cultured with CGF at different concentrations of LPS (0.1, 1, and 10 µg/ml) for 21 days. Then, using MTT and scratch assays, the cell viability and migration were examined. Osteogenic stimulation was evaluated by alkaline phosphatase (ALP) staining and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…In addition, Firouzi et al ( 2022) [29] reported that CGF enhanced bone regeneration induced by lipopolysaccharide in cell culture. Similarly, in our study, we observed that CGF regenerated pulpotomyinduced damage.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Firouzi et al ( 2022) [29] reported that CGF enhanced bone regeneration induced by lipopolysaccharide in cell culture. Similarly, in our study, we observed that CGF regenerated pulpotomyinduced damage.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Firouzi et al (2022) used a fibrin scaffold enriched with growth factors to assess the proliferation and differentiation of DPSCs under LPS-induced inflammatory conditions. They observed that DPSCs treated with LPS (1 µg/mL) on the fibrin scaffold promoted the release of pro-inflammatory cytokines such as TNF-α, which supported cell proliferation and migration during dental pulp inflammation [56].…”
Section: Effect Of Bacterial Lps On the Biological Characteristics Of...mentioning
confidence: 99%
“…Therefore, researchers have sought molecules to improve the regenerative process of DPSCs in LPS-induced inflammation. Firouzi et al (2022) observed that the use of concentrated growth factors promoted the release of cytokines such as TNF-α, which positively affected proliferation, migration, and odonto/osteogenic differentiation in DPSCs [56]. Another approach explored involves analyzing the behavior of DPSCs in interaction with bioactive materials to develop strategies in pulp therapy.…”
Section: Effect Of Bacterial Lps On the Biological Characteristics Of...mentioning
confidence: 99%
“…The chemokine receptor CXCR3 (CD183) was found on 30% of the adherent (ADH)-DPSCs [23], associated with neuroinflammatory responses and their potential involvement in homing neural progenitors to sites of brain damage [120]. Another study showed that human-concentrated growth factors (hCGFs) alone and in combination with LPS increased DPSC migration and osteogenic differentiation [121]. A conditioned medium, such as human gingival fibroblast-conditioned medium (hGF-CM), increased the migration, proliferation, cell viability and odontogenic differentiation of DPSCs after H 2 O 2 exposure [44].…”
Section: The Hdpsc Fatementioning
confidence: 99%